Sensitive Surface-Enhanced Raman Scattering (SERS) Detection of Nitroaromatic Pollutants in Water. Issue 7 (July 2014) - Wang, Menghan; De Vivo, Benedetto; Lu, Wanjun; Muniz-Miranda, Maurizio
The increasing and urgent demand for clean water requires new approaches for identifying possible contaminants. In the present study, polymer substrates with embedded silver nanoparticles are employed to reveal the presence of traces of nitroaromatic compounds in water on the basis of the surface-enhanced Raman scattering (SERS) effect. These platforms provide an easy and sensitive method of detecting of low concentrations of these organic pollutants in contaminated water.